Characteristics of Marine Mammal Habitat in Bintuni Bay - Ari Gunawan Wardhana; Yonvitner, Yonvitner; Akmal, Surya Gentha (Pusat Kajian Sumberdaya Pesisir dan Lautan IPB, 2025)
Bintuni Bay is one of the most important areas in Eastern Indonesia with high ecological potential, especially for marine mammals. This study aims to observe the presence of marine mammals and analyse water quality characteristics in Bintuni Bay to understand the environmental dynamics that affect the presence of marine mammals. Marine mammal observations were conducted along a predetermined pathway and seawater quality sampling was conducted at 16 points. Environmental parameters analysed included temperature, salinity, turbidity, dissolved oxygen (DO), chlorophyll-a and depth. Parameter determination was based on previous studies of key environmental parameters for marine mammal habitat and available data. Results showed that marine mammals in Bintuni Bay were found in the turbidity interval of 0.2 -16.7 NTU, temperature 24.7-27.4 0C, salinity 21.9 - 29.3 ppt, dissolved oxygen 4.10 - 6.30 mg/L, chlorophyll-a 5.38-49.10 µg/L and depth 10-51 m. This data can be utilized to conduct better environmental management for marine mammals as economic activities in Bintuni Bay increase in the future.